Dimensional changes of buccal bone plate in immediate implants inserted through open flap, open flap and bone grafting and flapless techniques: A cone‐beam computed tomography randomized controlled clinical trial. Issue 12 (11th September 2019) - Grassi, Felice Roberto; Grassi, Roberta; Rapone, Biagio; Alemanno, Gianfranco; Balena, Alessandro; Kalemaj, Zamira
Abstract: Objectives: To assess through cone‐beam computed tomography (CBCT) buccal alveolar bone alterations after immediate implant placement using the following techniques: open flap and grafting (flap‐graft), open flap and no grafting (flap‐nograft) and flapless and no grafting (noflap‐nograft). Materials and methods: This was a three‐armed parallel group randomized clinical trial with allocation ratio 1:1:1. Patients were eligible in case they needed immediate implant replacing teeth in maxillary premolar area, with sufficient buccal bone support. CBCT was performed immediately after the intervention and 6 months later. The main outcomes were CBCT measurements performed at apical (A‐EA), medial (M‐EM) and external and internal implant bevel level (B‐EB, B‐IB) and vertical defect depth (DP). Pain and discomfort, time of surgery and complications were recorded. Differences between groups were estimated through ANOVA tests and post‐hoc Scheffe's analysis for pairwise comparisons. Multiple regressions were conducted to estimate influence of gingival biotype and baseline marginal gap dimension. Results: Forty‐five patients were recruited and randomized to treatments with one lost to follow‐up. Analysis of variance showed that the effect of treatment technique was not relevant for all horizontal and vertical outcomes. The three techniques exhibited almost complete fill of marginal gap, with a mean residual vertical gap of 0.27 mm and horizontal gap of 0.5 mm. Regression models indicated a positive effect of thick biotype on gap filling and dimensional bone reduction. The noflap‐nograft technique resulted less painful. Conclusions: The option of noflap‐nograft surgery in post‐extraction implants allows for minimal surgical intervention with comparable buccal bone changes and gap filling after a follow‐up of 6 months in sites with sufficient buccal bone support.